Success Factors for the Implementation of an ERP and the Improvement of Financial Control in a Local Clinic - Cano Lengua, Miguel Angel (2023)
This research work was carried out in an important clinic located in the city of Lima that presented difficulties in its system: collections, payments, and payroll, affecting accounting information for the correct preparation of financial statements. Other internal deficiencies were the medical history report and the hospital services. The deficient system did not help in internal control processes and activities, obtaining problems such as sanctions before the National Health Superintendence, deficiencies in collections, inaccurate reporting of accounts payable and unreliable accounting records. The objective of this research is to expose the improvement made through an ERP, such as the accounting operational traceability, the integrity of the information and the provision of the information when being online. The methodology used was applied due to the experience in the sector executing the ERP to the solution of the company's problem presented and explanatory since the interaction with several collaborators allowed us to carry out the research scheme, the development and culmination of it. The results have been various, such as verification of the usefulness of the ERP, as well as the reduction of high-impact fines before supervisory bodies, the correct execution of the various means of payment, operating with local and foreign currency, the use of mobile tools, economic reduction in the payroll and finally comply with the banking law. For the investigation, the case of treasury and collections was taken and how it influences the accounting area to evaluate the benefits of the ERP.